2007
DOI: 10.1152/ajpgi.00422.2007
|View full text |Cite
|
Sign up to set email alerts
|

SMIT2 mediates all myo-inositol uptake in apical membranes of rat small intestine

Abstract: Aouameur R, Da Cal S, Bissonnette P, Coady MJ, Lapointe J-Y. SMIT2 mediates all myo-inositol uptake in apical membranes of rat small intestine. Am J Physiol Gastrointest Liver Physiol 293: G1300-G1307, 2007. First published October 11, 2007; doi:10.1152/ajpgi.00422.2007.-This study presents the characterization of myo-inositol (MI) uptake in rat intestine as evaluated by use of purified membrane preparations. Three secondary active MI cotransporters have been identified; two are Na ϩ coupled (SMIT1 and SMIT2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…Standard treatments of this neurological disease include lithium salts, (e.g., lithium chloride), carbamazepine, and valproate (26). Studies have hypothesized both that lithium can inhibit myo- inositol biosynthesis and that it can decrease the activity of high-affinity myo- inositol transport, along with 2 other bipolar therapies, valproate and carbamazepine, based on studies in cultured astrocytes (26). We evaluated the effects of these drugs on the uptake of radiolabeled myo- inositol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Standard treatments of this neurological disease include lithium salts, (e.g., lithium chloride), carbamazepine, and valproate (26). Studies have hypothesized both that lithium can inhibit myo- inositol biosynthesis and that it can decrease the activity of high-affinity myo- inositol transport, along with 2 other bipolar therapies, valproate and carbamazepine, based on studies in cultured astrocytes (26). We evaluated the effects of these drugs on the uptake of radiolabeled myo- inositol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary assays have shown that linearity of uptake was maintained for ϳ60 min under all conditions used throughout this study (tracer or saturating conditions, isotonic and hypertonic media), which validated the chosen uptake time of 30 min. Discrimination between SMIT1 and SMIT2 activities was performed, as presented elsewhere (1,4,31), using specific uptake conditions. This strategy, which compares activities in the absence of inhibitor (total uptake) to those in the presence of either 100 mM L-fucose (blocking condition for SMIT1) or saturating MI (10 mM, blocking both SMIT1 and SMIT2), enables a functional isolation of both SMIT1 (subtracting L-fucose condition from total) and SMIT2 (subtracting saturating condition from Lfucose).…”
Section: Methodsmentioning
confidence: 99%
“…The solute carrier family 5 (SLC5A) comprises of six Na + -glucose cotransporters (sodium glucose-linked transporters, SGLT; ref. 54), of which SGLT5 has not been functionally characterised so far and SGLT6 is, in fact, an intestinal and renal Na + -myo-inositol transporter (therefore renamed SMIT2) with very low affinity to glucose (1,29). The second family of glucose transporters is SLC2A, comprising of 13 members (GLUT1- GLUT 13); the last member (GLUT13) again being a myo-inositol transporter (renamed HMIT; ref.…”
mentioning
confidence: 99%